2016
DOI: 10.1007/s00784-015-1708-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasonic tip and root-end filling material on bond strength

Abstract: Root-end preparation with the CVD tip positively influences the bond strength of root-end filling materials. MTA Angelus and experimental MTAS present bond strength to be used as root-end filling materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In addition, the difference observed in relation to the presence of debris may also have a key impact on the prognosis as it interferes with the adhesion of calcium silicate-based cements to the dental walls. Vivan et al [ 62 ] found highest bond strength values when preparing with CVD tips, irrespective of the root-end filling material used, meaning that root-end preparation with the CVD tips positively influences the bond strength of root-end filling materials.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the difference observed in relation to the presence of debris may also have a key impact on the prognosis as it interferes with the adhesion of calcium silicate-based cements to the dental walls. Vivan et al [ 62 ] found highest bond strength values when preparing with CVD tips, irrespective of the root-end filling material used, meaning that root-end preparation with the CVD tips positively influences the bond strength of root-end filling materials.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the BS of endodontic filling materials should be as high as possible, not only to ensure efficient root canal sealing but also to ensure long-term endodontic treatment success. 6,21,22 Furthermore, the bonding interface must remain intact over time and not compromise clinical procedures, such as the removal of part of the sealing material for the installation of root canal posts, because the teeth are subjected to mechanical forces that can displace the sealing material beyond root canal limits. 23,24 Therefore, in the present study, the BS of the filling material was evaluated after 24 h and 6 months of storage in water.…”
Section: Discussionmentioning
confidence: 99%
“…8 The factors that play a role in adhesion of root end fillings are the type of material used, burs used for the cavity preparation and the pH value of the environment. 9,10 In this study push out bond strength of two calcium silicate based materials i.e ; MTA and Biodentine were used and compared against Bone Cement. The characteristic of calcium silicate-based materials is to precipitate carbonated apatite in the presence of tissue fluids, followed by the formation of interfacial layer and tag like structures in the dentin.…”
Section: Discussionmentioning
confidence: 99%